If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + 2) = 5x + -10 Reorder the terms: 3(2 + x) = 5x + -10 (2 * 3 + x * 3) = 5x + -10 (6 + 3x) = 5x + -10 Reorder the terms: 6 + 3x = -10 + 5x Solving 6 + 3x = -10 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 6 + 3x + -5x = -10 + 5x + -5x Combine like terms: 3x + -5x = -2x 6 + -2x = -10 + 5x + -5x Combine like terms: 5x + -5x = 0 6 + -2x = -10 + 0 6 + -2x = -10 Add '-6' to each side of the equation. 6 + -6 + -2x = -10 + -6 Combine like terms: 6 + -6 = 0 0 + -2x = -10 + -6 -2x = -10 + -6 Combine like terms: -10 + -6 = -16 -2x = -16 Divide each side by '-2'. x = 8 Simplifying x = 8
| .4x=8 | | 5(y+3)+2(8-3y)=-3 | | 8v-34=-2v-3 | | 3(x-2)-x=8 | | .24x-.38(x+2)=.34(x+4) | | .35(20)+.45y=.125(200) | | m^2-2M-1=0 | | 11x^2+19x-20=0 | | 7(3x-12)=6(3x-12) | | -7r^2+140r+100=0 | | 4x+2(x+1)=8 | | 6x-5y=7 | | log(x+2)+log(x-2)-log(x^3-8)= | | 6x-2(x-5)=22 | | 6(6t+1)=9(4t-3)+33 | | y=6x^2+bx+c | | 2n+4.1=8.5 | | 5y+22=4y-42 | | 15a^2-3a=3-7 | | 25-99x^2-4x^4=0 | | -1-(2+y)=-(4+y) | | x-2x-7x+11x=9 | | 24n^2-16n=0 | | 4x^2=8x-5 | | 3u^2+6=11u | | x(x-2)=4 | | 2x^3+6x^2+x-9=0 | | 3x-1y=5 | | x^2+6x+196=0 | | x/(-3)-12=-15 | | 15y+14=2y+8y+12 | | -2x+11=13 |